THE DEFFERENCE PLAK ACCUMULATION IN DENPASAR HIGH SCHOOL STUDENTS WITH FIXED ORTHODONTIC APPLIANCES BEFORE AND AFTER OHMM WERE GIVEN - Anak Agung Gede Agung; I Nyoman Wirata; Ni Made Widhiasti (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
The correct tooth brushing behavior on fixed orthodontic appliances users is a form of oral hygiene care behavior to prevent the plaque accumulation that will minimize the occurrence of periodontal disease. It takes Oral Hygiene Motivation Methods (OHMM) in the form of instruction, adequate equipment and materials, and also patient motivation.   The purpose of this study was to analyze the toward plaque accumulation in  Denpasar high school students with fixed orthodontic appliances before and after OHMM were given.  This experimental study with Pre-Post Test without Control design was conducted on 124 high school students in Denpasar who use  fixed orthodontic appliances. The study datas are  the examination of Plaque Index before and 21 days after the OHMM were given.The results showed that  mean scores of Plaque Index in the pre and post examinatons were respectively of 1.6 and 0.8. Based on an analysis using Wilcoxon Match Pairs Test showed Plaque Index between before and after OHMM were respectively p = 0.00 (p 0.05).A Conclusion of  the high school students in Denpasar who uses  fixed orthodontic appliances after OHMM were given study are the Plaque Index decreased with mild criteria. The Plaque Index significantly different between before and after OHMM were given